2022
DOI: 10.1038/s41523-022-00455-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intestinal microbiota in postmenopausal oestrogen receptor-positive breast cancer patients treated with (neo)adjuvant chemotherapy

Abstract: This clinical study explored the associations between the intestinal microbiota, chemotherapy toxicity, and treatment response in postmenopausal oestrogen receptor positive breast cancer patients.Oestrogen receptor positive postmenopausal breast cancer patients were prospectively enroled in a multicentre cohort study and treated with 4 cycles of (neo)adjuvant adriamycin, cyclophosphamide (AC) followed by 4 cycles of docetaxel (D). Patients collected a faecal sample and completed a questionnaire before treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…A second study based on the CANTO cohort collected fecal samples before (n = 76) and after (n = 45) chemotherapy from breast cancer patients and performed analyses combining the neoADJ and ADJ groups 16 . In the Dutch study, alpha diversity decreased after completion of chemotherapy (observed species decreased 9.6% [ p = 0.042] and Shannon index decrease 2.5% [p = 0.21]) 15 whereas in the CANTO study, species richness increased ( p = 0.033) after completion of chemotherapy (p = 0.033). 16 However, because these two previous studies did not investigate changes in alpha diversity separately by type of chemotherapy and our results suggest increased in alpha diversity in the neoADJ group but decreases in the AD group, additional studies by type of chemotherapy will be needed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A second study based on the CANTO cohort collected fecal samples before (n = 76) and after (n = 45) chemotherapy from breast cancer patients and performed analyses combining the neoADJ and ADJ groups 16 . In the Dutch study, alpha diversity decreased after completion of chemotherapy (observed species decreased 9.6% [ p = 0.042] and Shannon index decrease 2.5% [p = 0.21]) 15 whereas in the CANTO study, species richness increased ( p = 0.033) after completion of chemotherapy (p = 0.033). 16 However, because these two previous studies did not investigate changes in alpha diversity separately by type of chemotherapy and our results suggest increased in alpha diversity in the neoADJ group but decreases in the AD group, additional studies by type of chemotherapy will be needed.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that the last fecal sample was collected ~100 days after completion of chemotherapy in our study but it is not clear when the fecal sample was collected after completion in the previous two studies. 15 , 16 It is reasonable to speculate that changes in the gut microbiome immediately after completion of chemotherapy may differ from gut microbiome assessed a few months after completion of chemotherapy. A third study included 24 breast cancer patients with HER2+ disease who received neoADJ trastuzumab-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, since we observed that gemcitabine alone [10,30] or combined with nab-paclitaxel, affects gut microbiota in mouse models of PDAC and since it was reported that chemotherapy reshapes the gut microbiota in human patients suffering from different types of cancers [31][32][33][34], often promoting an overgrowth of inflammatory Proteobacteria [31,33], we plan to investigate, in the next future, the microbiota composition of PDAC patients before and after receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These microbial changes can in turn influence the presence and severity of GI symptoms. Aarnoutse et al (2022) collected stool samples and symptom data from post-menopausal breast cancer patients receiving neoadjuvant Adriamycin, Cyclophosphamide, and Docetaxel chemotherapy. They found that patients reporting diarrhea during treatment had a significantly lower observed species richness compared to patients who did not have diarrhea during treatment.…”
Section: Introductionmentioning
confidence: 99%